The Effect of Murabahah Financing for Civil Servants on Jambi Syariah Bank Income - Lisa, Novita (Zabags International Journal of Economy, 2023)
This research aims to develop micro, small and medium enterprises (MSMEs) at Bank Syariah Mandiri Jambi Area. Even with this strategy alone, Bank Syari'ah Mandiri Jambi Area has played an active role in the development of MSMEs in Jambi City by helping the growth and development of MSME businesses. Previously BSM focused on providing business capital only. However, currently, BSM Area Jambi has played an active role in providing business assistance, such as encouraging business permits for businesses that do not yet have official permits from the government. Factors that support BSM's contribution in financing MSMEs in Jambi City are religious adherents supporting MSMEs in choosing BSM financing and government policy in the form of KUR as a relief financing for MSMEs. Meanwhile, the obstacles from the customer side are difficulties in assessing feasible and bankable MSMEs that meet bank requirements, limited access to information for MSMEs regarding existing financing facilities causing low public interest in BSM financing facilities and difficulties in fostering MSME management such as financial separation between personal and business finances.